Issues of Society Development in the Zoroastian Religion (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
In this article, the issues of social protection of the family in the "Zoroastrianism" religion are discussed. The article focuses on the role of the family in society, women's issues, strong social policy, and issues of social protection. Conclusions on strengthening social protection of the family are also given.